Influência do posicionamento terapêutico sobre os indicadores cardiorrespiratórios e atividade motora de recém-nascidos pré-termo em suporte respiratório - Quoos, Marcia (2017)
The preterm newborn presents a compromise in gas exchange due to pulmonary immaturity and the disadvantages in respiratory mechanics, presenting a higher risk of developing neonatal respiratory distress syndrome (RDS). The therapeutic position of newborns is a type of non-invasive intervention used in the treatment of respiratory diseases, benefiting the neurosensory and psychomotor development. In order to investigate the benefits of the different positions of the preterm newborn, the purpose of this study was to investigate the influence of the therapeutic positioning on the cardiorespiratory indicators and motor activity (MA) of the preterm newborn in use respiratory support invasive or not, during the acute phase of respiratory distress. It is a cross-sectional, observational, prospective study with a cross-over and randomized design, performed with preterm newborns with clinical syndrome of respiratory distress, birth weight below 2.000 g, between the 3rd and 7th day of life , in use respiratory support invasive (IMV) or noninvasive (NIV), between July 2016 and June 2017. The newborns were maintained at each body position (supine, prone, right and left lateral) for 45 minutes and cardiorespiratory indicators (heart rate (HR), respiratory rate (RR), peripheral oxygen saturation (SpO2) and MA were recorded in intervals of 7 minutes, obtaining a total of five records in each position. Analysis of variance for repeated measures (ANOVA) and Friedman test, with post hoc tests were used to compare the cardiorespiratory indicators in the different positions. Pearson correlation was performed to verify statistical dependence between MA and HR, in the different positions. Statistical significance was considered when p<0.05. We studied thirty-three preterm newborns, 12 in the IMV group, with a gestational age (GA) of 27.0 (± 1.5) weeks and a weight of 837 (± 284) grams, and 21 in the NIV group, with a GA of 30.5 (± 1.9) weeks and weight of 1297 (± 416) grams. In the NIV group, there was a significant increase in SpO2 when compared to the prone positions vs. supine -1.1 (95%CI -2.0 to -0.2), p=0.017, prone vs. right lateral 1.1 (95%CI 0.2 to 1.9), p=0.015 and prone vs. left lateral 1.3 (95%CI 0.5 to 2.2), p=0.003. In the IMV group, SpO2 presented a significant increase only when compared to the prone position vs. supine -1.5 (95%CI -2.5 to -0.5), p=0.010. The HR of the preterm newborns of the NIV group presented a significant decrease when compared to positions left lateral vs. right lateral (p=0.032) and RR remained within normal range during the different positions, but did not present significant differences in both groups. The prone position also presented a lower MA when compared to the other positions (p<0.001). Conclusion: the results showed that the prone position was beneficial for preterm infants in respiratory support invasive and noninvasive, during the acute phase of respiratory distress, standing out from the others, since it increased peripheral oxygenation, providing comfort, evidenced by the reduction of MA.